Do you want a 28% pay rise, 1986 (1986)
1986 1960-2000 "Do you want a 28% pay rise, 1986" [EP0153], 1986 Poster issued as part of the TASS 'Men's Pay for Women' campaign. TASS was formerly the Amalgamated Union of Engineering Workers. Technical, Administrative and Supervisory Section.